249.117,50€ Research Grant ‘RESTART 2016 – 2020'. Call identifier: INFRASTRUCTURE/1216, Programme: EXCELLENCE HUBS, Pillar ' II. Sustainable RTDI System' - Keivanidis, Panagiotis E. (My University, 2026)
Coordinator of research project 'Low Photon-Energy Up-Conversion induced Sensitized Photocurrent Generation in Organic Photodiodes' (LOSPHOGEN), ref: EXCELLENCE/1216/0010.‘RESTART 2016 – 2020', Call identifier: INFRASTRUCTURE/1216, Programme: EXCELLENCE HUBS, Pillar ' II. Sustainable RTDI System'. Co-financed by the European Regional Development Fund and the Republic of Cyprus through the Research and Innovation Foundation.
Keywords: Natural sciences